Minimal incision palatoplasty with or without muscle reconstruction in patients with isolated cleft palate—a cephalometric study at 5 and 10 years. (16th November 2018) - Parikakis, Konstantinos; Larson, Ola; Karsten, Agneta
Summary: Objective: To compare differences in facial growth in patients with isolated clefts of the hard and/or soft palate treated with the minimal incision technique without (MI) or with muscle reconstruction (MMI). Subjects and method: A consecutive series of 170 Caucasian children born with isolated cleft palate were studied. Individuals with other craniofacial malformations, apart from Pierre Robin sequence (PRS), were excluded. The patients were treated surgically with MI ( n = 85) or MMI ( n = 85) palatoplasty (mean age: 13 months) and divided further into two subgroups: clefts within the soft palate only (small cleft, n = 51) and within the hard and soft palate (big cleft, n = 119). A retrospective evaluation at 5 (mean 5.4) and 10 (mean 10.3) years was performed using lateral cephalograms. Twelve skeletal and one soft tissue measurement was evaluated. Both 95% and 99% confidence intervals were calculated, two-way ANOVA and mixed model analysis was performed including/excluding PRS. Results: At 5 years, statistically significant increased inclination of the palatal plane in the big MMI cleft group ( P < 0.01), increased posterior upper face height ( P < 0.01), and longer mandibular length ( P < 0.001) in the small MI cleft group was observed. At 10 years, statistically significant increased inclination of the palatal plane ( P < 0.001), decreased posterior upper face height ( P < 0.001), and longer palatal length ( P < 0.01) was seen in the big MMI group. Limitations: Retrospective single centre study, limited sample size, three surgeons. Conclusion: Minor differences in craniofacial morphology were found between patients with isolated clefts treated with MI or MMI technique and between small and big cleft lengths.